Religious pluralism, state and society in Asia - Formichi, Chiara (Routledge religion in contemporary Asia series, 2014)
"Taking a critical approach to the concept of 'religious pluralism', this book examines whether Asian societies favour one religion over a number of different religious traditions. It looks at the quality of relations that emerge in encounters among people of different religious traditions or among people who hold different visions within the same tradition. Chapters focus in particular on the places of everyday religious diversity in Asian societies in order to explore how religious groups have confronted new situations of religious diversity. The book goes on to explore the conditions under which active religious pluralism emerges (or not) from material contexts of diversity"--